Pengembangan Modul Pembelajaran Multimedia untuk Meningkatkan Minat dan Pemahaman Konsep Mahasiswa Prodi Pendidikan Informatika - Kholisho, Yosi Nur (Universitas Hamzanwadi, 2017)
The purpose of this research is to develop and produce product in the form of multimedia instructional subjects for students on informatics education course and to know the effectiveness of modules developed based on responses of student interest to learning and learning outcomes. The method used in this research is Research and Development. Based on data from media and product expert validation, it can be seen that the product in the form of multimedia learning module for students can be categorized as